The role of B-adrenergic blockers and calcium antagonists on the inotropy of the isolated rat heart after cardioplegic arrest - Hattingh, P. W.(Pieter Wilhelm) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1991.